Photocatalytic Th(IV) removal: Unleashing the potential of amidoxime-modified graphitic carbon nitride photocatalyst - Yussuf N.M.; Ismail A.F.; Mohamed N.A.; Mat Teridi M.A. (Elsevier B.V., 2025)
g-C3N4-AX photocatalyst was synthesized using a hydrothermal approach, with urea as a precursor, for the removal of Th(IV) in aqueous solution. The results of the experiment indicated that the addition of amidoxime to g-C3N4 altered its photocatalytic characteristics, resulting in a narrower band gap reduced from 2.75 eV to 2.7 eV, and faster formation of electron-hole pairs. The g-C3N4-AX photocatalyst exhibited remarkable uptake capacity with 71.09 mg.g?1 within 120 min. The excellent performance of g-C3N4-AX was mainly attribute to its effective absorption of visible light, facilitated by the narrow band gap. Therefore, this study proposes the potential of g-C3N4-AX can be efficiently adapted as a visible light-responsive catalyst for the application in radioactive effluent treatment. ? 2023 Elsevier B.V.